2021
DOI: 10.1037/str0000214
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between psychological contract violation, occupational stress, and well-being in police officers.

Abstract: The emotional reactions arising from the breaking of promises by or the failure of organizations to meet one or more obligations, as perceived by an employee, is termed psychological contract violation (PCV) and is purported to have negative consequences for the employee and the employer. This article explores the impact of feelings of perceived violation on the employees' occupational stress and well-being using the measures of psychological contract violation, occupational stress, and job-related well-being.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…Study found positive correlation between health risk and age (0.414 * ), income (0.017 * * ), and work experience (0.558 * * ). Several studies found same results (7,23,53,59). Thus, hypothesis 3a is accepted.…”
Section: General Illnessesmentioning
confidence: 61%
“…Study found positive correlation between health risk and age (0.414 * ), income (0.017 * * ), and work experience (0.558 * * ). Several studies found same results (7,23,53,59). Thus, hypothesis 3a is accepted.…”
Section: General Illnessesmentioning
confidence: 61%
“…Such a type of turnover occurs more often with junior employees than seniors (Said et al, 2021). The breach of psychological contracts creates psychological stress and emotional exhaustion for employees (Duran et al, 2021). Such a breach may lead to loss of organizational resources, where an employee is considered one of the main organizational resources.…”
Section: Psychological Contract Fulfillmentmentioning
confidence: 99%
“…police officers, a major source of police stress was identified as inadequate equipment to perform their duties resulting from austerity cuts (Duran et al, 2019). Duran, Woodhams and Bishopp (2020) also reported stress was linked to how police employees perceive unfairness when their contributions are not fully reciprocated or valued.…”
Section: Emerging Covid19 Researchmentioning
confidence: 99%